Pig Xenotransplantation in the Qur’an: Application of Jasser Auda’s Theory of Maqāṣid al-Sharī‘ah - Siti Khodijah; Iffah Iffah (Refleksi: Jurnal Kajian Agama dan Filsafat, 2023)
This research discusses the interpretation of pig xenotransplantation in the Qur'an according to the commentators and according to the theory of maqāṣid al-sharī‘ah by Jasser Auda. This research uses a type of library research which is presented using a qualitative research model with descriptive method. The results of the research show that the interpreters have different opinions regarding the prohibition of pork in the context of consumption (eating) alone or the prohibition of pork in all forms of use. Quraish Shihab is an interpreter who allows pig xenotransplantation. Based on the application of Jasser Auda’s theory of maqāṣid al-sharī‘ah theory, it was found that the systems approach containing six features, can be contextualized in analyzing the problem of pig xenotransplantation. In this case, pig xenotransplantation is permitted because of the urgency justified by sharia (ḍarurah shar’iyah), for which is the last alternative in efforts to preserve lives. Accordingly, although both of the results allow pig xenotransplantation, in this research it is explained how the steps or approaches were used to conclude the permissibility of pig xenotransplantation.